NATURAL SCHOOLS: ALTERNATIVE EDUCATION OF STUDENTS IN 21ST CENTURY LIFE SKILLS - Nanda Ayu Setiawati; Elvi - Mailani; Fadhilla Syam Nst; Edy - Surya (FORUM PAEDAGOGIK, 2023)
These 21st-century skills must be developed early on in students through education so that at their productive age, they can live properly in the world community. School of Nature is used as an alternative education in 21st-century life skills. The purpose of this study is to inform Indonesian people, especially the government, educators, students, and child observers about the importance of schools that carry child-friendly concepts, and the existence of the JIGS Medan Nature School in providing educational facilities for students in 21st-century life skills. This research is interpretative qualitative research. In this study, primary data was taken from observations and interviews at the Natural School from observations and discussions at the JIGS Natural School in Medan, and secondary data was obtained from a literature study. The analysis of the text used is qualitative in nature. The results of the research are that the concept that is presented carefully makes Sekolah Alam worthy of being an offered solution for child-friendly schools, consisting of anti-bullying programs such as Network People and Nursing which are implemented in almost all Natural Schools, for example, is a form of objective in a child-friendly concept.